Analyzing the shear performance of dapped wet vertical wall-to-wall connection - Amril Hadri Jamaludin,; Noorsuhada Md Nor,; Amir Khomeiny Ruslan,; Soffian Noor Mat Saliah,; Ahmad Syauqi Md Hassan,; Mohd Azrizal Fauzi,; Shahrum Abdullah,; Fatma Sakinah Razali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The utilization of precast wall panels has gained prominence due to its potential for enhancing construction speed, quality, and sustainability. One critical aspect of precast construction is the connection between wall panels, where it is one of the proven to be the weakest link in the system. Rigidity of the connection between panels was also a point of concern. This research aims to investigate the mechanical performance of the dapped wet connection model in the vertical wall-to-wall connection in application for precast wall panels, particularly focusing on shear load considerations. The investigation includes experimental testing that includes three pair of specimens subjected to shear loading to evaluate their shear strength capacity, strain, and connection flexibility behaviour as well as the resulting crack propagation throughout the test. The test was verified through Acoustic Emission (AE) technique using Energy (eu) parameter. The proposed sample tested shows a significant improvement compared to the control sample with respect to maximum shear strength, however it displays a brittle behaviour by developing multiple cracks along the connection interface and having a significant shear failure at the end of the test. The findings of this study will contribute to a better understanding of the behavior of dapped wet connection and provide preliminary guidance for their design in precast concrete wall panels.